eBird, Expertise, & the Technological Mediation Of Citizen Science - Walker, John; Stellinga, Luuk; M. van Leersum, Catharina (Journal of Human-Technology Relations, 2023)
Technological advances in application development and open science continue to revolutionize and create new forms of citizen science. However, as of today, the role of technology in citizen science has remained relatively unexplored. In this essay, we pose the question of how citizen science apps shape the practice of citizen science, looking specifically towards the popular birding app eBird as a case study. Through the citizen science practices co-shaped by eBird, this essay will dive into the functions of the application, how it can be regarded as shaping human-technology relations and the impacts this has on the relationship between citizen (scientist) and expert. After building the case for eBird’s influential role in citizen science with regard to birding, the discussion pivots towards the future of citizen science as a democratic process shaped by the technologies used to gather and share scientific data. This essay concludes by asking how a more democratic understanding of citizen science can be developed through both empowering citizens to not just participate in data gathering, but also to help interpret it in new and informed ways with the citizens’ own interests in mind.